Efficacy of emergent transcatheter transplantation of stem cells for treatment of acute myocardial infarction (TCT-STAMI). Issue 12 (14th June 2006) - Ge, J; Li, Y; Qian, J; Shi, J; Wang, Q; Niu, Y; Fan, B; Liu, X; Zhang, S; Sun, A; Zou, Y
Abstract : Objective: To study whether emergent intracoronary autologous bone marrow cell transplantation (BMT) is applicable for the treatment of acute myocardial infarction (AMI). Methods: 20 patients admitted within 24 h after the onset of a first AMI were randomly allocated to receive intracoronary autologous BMT (n  =  10) or bone marrow supernatant (controls, n  =  10) immediately after primary percutaneous coronary intervention. Left ventricular ejection fraction (LVEF), left ventricular end diastolic internal diameter (LVDd) and myocardial perfusion defect scores were examined respectively by echocardiography and single-photon emission computed tomography at one week and six months after AMI. Results: From one week to six months after AMI, LVEF was enhanced from mean 53.8 (SD 9.2)% to 58.6 (9.9)% (p < 0.05) in the BMT group but was unchanged in the control group (58.2 (7.5)% v 56.3 (3.5)%, p > 0.05); LVDd remained unchanged (52.5 (2.8) v 52.1 (3.2) mm, p > 0.05) in the BMT group but was significantly enlarged in the control group (50.4 (6.0) v 55.2 (7.1) mm, p < 0.05). Additionally, myocardial perfusion defect scores decreased from 21 (11) to 13 (10) (p < 0.01) in the BMT group but were unchanged in the control group (20 (14) v 17 (15), p > 0.05). Conclusion: Emergent intracoronary transplantation of bone marrow mononuclear cells after AMI is practicable, and it improved cardiac function, prevented myocardial remodelling and increased myocardial perfusion at six months' follow up.